Atmospheric Chemistry of tert-butylamine and AMP. (July 2017) - Antonsen, Simen; Bunkan, Arne J.C.; D'Anna, Barbara; Eichler, Philipp; Farren, Naomi; Hallquist, Mattias; Hamilton, Jacquiline F.; Kvarnliden, Hampus; Mikoviny, Tomáš; Müller, Markus; Nielsen, Claus J.; Stenstrøm, Yngve; et al.
Abstract: The atmospheric chemistry of (CH3 )3 CNH2 ( tert -butylamine, t BA) and (CH3 )2 (CH2 OH)CNH2 (2-amino-2-methyl-1-propanol, AMP) has been studied by quantum chemistry methods and in photo-oxidation experiments in the EUPHORE chamber in Valencia (Spain). Aerosol formation and composition has been quantified. Yields of nitramines and other products in the photo-oxidations have been determined and complete photo-oxidation schemes including branching between the major reaction routes have been obtained.